IIED: working for the environment - Technical Centre for Agricultural and Rural Cooperation (Technical Centre for Agricultural and Rural Cooperation, 1998)
Do you need to know more about the effects of air pollution on local food production? Does your community-based organisation face difficulties in becoming an effective stakeholder in discussions about forestry management with the government? Or...